Numerical Study of the Indoor Thermo-Hygrometric Behaviour of a new HVAC System for the Baroque Joanina Library of the University of Coimbra - Couto, Francisco Jorge Martins do (2024)
Dissertação de Mestrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia